Cariporide Attenuates Doxorubicin-Induced Cardiotoxicity in Rats by Inhibiting Oxidative Stress, Inflammation and Apoptosis Partly Through Regulation of Akt/GSK-3β and Sirt1 Signaling Pathway - Liao, Wenli; Rao, Zhiwei; Wu, Lingling; Chen, Yong; Li, Cairong (Frontiers in Pharmacology, 2022)
Background: Doxorubicin (DOX) is a potent chemotherapeutic agent with limited usage due to its cumulative cardiotoxicity. The Na+/H+ exchanger isoform 1 (NHE1) is a known regulator of oxidative stress, inflammation, and apoptosis. The present study was designed to investigate the possible protective effect of cariporide (CAR), a selective inhibitor of NHE1, against DOX-induced cardiotoxicity in rats. Methods: Male Sprague-Dawley rats were intraperitoneally injected with DOX to induce cardiac toxicity and CAR was given orally for treatment. The injured H9c2 cell model was established by incubation with DOX in vitro. Echocardiography, as well as morphological and ultra-structural examination were performed to evaluate cardiac function and histopathological changes. The biochemical parameters were determined according to the manufacturer’s guideline of kits. ROS were assessed by using an immunofluorescence assay. The serum levels and mRNA expressions of inflammatory cytokines were measured by using ELISA or qRT-PCR. Cardiac cell apoptosis and H9c2 cell viability were tested by TUNEL or MTT method respectively. The protein expressions of Cleaved-Caspase-3, Bcl-2, Bax, Akt, GSK-3β, and Sirt1 were detected by western blot. Results: Treatment with CAR protected against DOX-induced body weight changes, impairment of heart function, leakage of cardiac enzymes, and heart histopathological damage. In addition, CAR significantly attenuated oxidative stress and inhibited the levels and mRNA expressions of inflammatory cytokines (TNF-α, IL-6, IL-18, and IL-1β), which were increased by DOX treatment. Moreover, CAR significantly suppressed myocardial apoptosis and Cleaved-Caspase-3 protein expression induced by DOX, which was in agreement with the increased Bcl-2/Bax ratio. Also, DOX suppressed phosphorylation of Akt and GSK-3β, which was significantly reversed by administration of CAR. Furthermore, CAR treatment prevented DOX-induced down-regulation of Sirt1 at the protein level in vitro and in vivo. Finally, Sirt1 inhibitor reversed the protective effects of CAR, as evidenced by reduced cell viability and Sirt1 protein expression in vitro. Conclusion: Taken together, we provide evidence for the first time in the current study that CAR exerts potent protective effects against DOX-induced cardiotoxicity in rats. This cardio-protective effect is attributed to suppressing oxidative stress, inflammation, and apoptosis, at least in part, through regulation of Akt/GSK-3β and Sirt1 signaling pathway, which has not been reported to date.